Competitions among OTT TV Platforms and Traditional Television in Taiwan: A Niche Analysis - Yi-Ning Katherine Chen (International Telecommunications Society (ITS), 2017)
This study examines if OTT TV is a complement or a substitute for traditional TV. By categorizing satisfaction into seven dimensions, this study adopts niche theory to look at the aspects of gratification toward OTT TV's complementarity of or replacement of cable TV. Following an online survey conducted during March 2016, 620 qualified responses were collected. The results show that the giant western OTT platforms overshadow the local OTT players. In terms of niche breadth, our findings present that OTT TV scores higher than traditional TV for all seven dimensions, with the greatest difference manifested on the dimension of convenience. For the niche overlap, our findings show that OTT and traditional TV share a high level of similarity on amusement and ease of use. Overall, OTT TV's competitive superiority surpasses that of traditional TV in all dimensions. Implications for research and practices are discussed herein.
Keywords: 330; OTT; niche theory; viewing behavior; TV; streaming industry